From Cubs to Lions: A Six Stage Model of Child Socialization into the Islamic State. (3rd July 2017) - Horgan, John G.; Taylor, Max; Bloom, Mia; Winter, Charlie
ABSTRACT: Using the Islamic State in Iraq and al-Sham (ISIS) as a case study, we explore the process by which children evolve from novice recruits to fully fledged members of a violent extremist movement. From currently available data, we propose six stages of child socialization to ISIS— Seduction, Schooling, Selection, Subjugation, Specialization, and Stationing . Furthermore, we explore this process in the context of "Community of Practice" (COP) as developed by Wenger and Lave. COP models highlight how newcomers learn and pass through degrees of involvement from the periphery of an organization to the inside. In subsequent research, Hundeide highlighted how "contracts of deep commitment" and "conversion" constitute important social and psychological elements of communities of practice. We regard such qualities as intrinsic to children's involvement in ISIS. We conclude with implications drawn from the disengagement and reintegration experiences of former child soldiers in other contexts.